The Implementation of Good Corporate Governance in Maintaining Financial Stability at Perumda BPR Bank Kota Kediri - Popy Setyaningrum (Transpublika Publisher, 2026)
The implementation of Good Corporate Governance (GCG) is considered a crucial mechanism for ensuring transparency, accountability, and sustainability in financial institutions, including regionally owned rural banks (BPRs). However, challenges related to governance practices, political intervention, and organizational capacity often affect the effectiveness of GCG in maintaining financial stability. This study aims to analyze the implementation of Good Corporate Governance (GCG) and its impact on financial stability at Perumda BPR Bank Kota Kediri. This qualitative study using a case study approach collected data through in-depth interviews with board of commissioners, directors, internal auditors, and external parties, as well as analysis of internal financial reports. The results show that the implementation of the five GCG principles which are transparency, accountability, responsibility, independence, and fairness remains formal and not yet fully substantive. Key obstacles include local government ownership structure leading to intervention, limited Human Resources (HR) capacity, hierarchical organizational culture, and suboptimal information technology systems. The impact of suboptimal GCG implementation on financial stability is reflected in the still high non-performing loan (NPL) ratio, although it shows an improving trend from 45% (2019) to 23.49% (2023). Other indicators such as Return on Assets (ROA) and operational efficiency (BOPO) also show positive improvement. The conclusion emphasizes that the effectiveness of GCG in maintaining the financial stability of regionally-owned BPRs highly depends on internalizing governance principles into the organizational culture and reducing political intervention, in addition to complying with the formal structures set by the Financial Services Authority (OJK) regulations.